Acid system selection for damaged berea sandstone by oil base mud - 175527 Suresh Murugiah (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Petroleum Engineering) - Universiti Teknologi Malaysia, 2003